Das nicht so neue Tandem:: Gewalt und Globalisierung - Narr, Wolf-Dieter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
After the 11th of September the old and much too suppressed topic about the – causal?, dialectic? – relation between capital development and its newest stage, i.e. globalization and violence has to be taken up again. Going back to Marx´ famous and still very readable Part VIII of ‘Capital’ (The So-Called Primitive Accumulation) it will be argued, that the inbuilt violence of the capitalist development is increasing but not decreasing in the wake of its globalization. Therefore the search for alternatives has to be pushed forward much harder that it has been the case during the stupidifying discussion about the end of history.